PERANAN PERPUSTAKAAN SOEMAN HS DALAM MENINGKATKAN MINAT BACA MAHASISWA DI PEKANBARU - Melay, Ridwan Melay Ridwan; ', Rosmiati; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Library is an institution that plays a role in the development of interest in reading. It is very reasonable, the fact that the library is an entity that is directly related to various types of reading material. All of these reading materials by the library is not just for storage only. But, more than that these materials should be utilized as much as possible by library users. Libraries can be a tool to grow and increase interest in reading when the library can serve as a center of interest in reading. A comfortable and quiet library and characterize a friendly and fun place for children, adolescents and adults. The purpose of this study was to determine student reading in library Soeman HS, to examine the use of the library by students Soeman HS increase interest in reading, and the role of libraries Soeman HS in increasing student interest in reading. This research method is quantitative descriptive method. The location of research is Soeman HS library is located at the Sudirman No. 462 Pekanbaru. When the study for 3 months starting from the start until the exam thesis proposal seminar. Data collection technique used observation, questionnaires and interviews guided and tabulation of data contained in tabular form. Results of research in general researchers can say that the implementation of student interest in reading categorized quite good due to the efforts made to improve the student's own interest in reading. In addition, use of the library by students Soeman HS can be quite good because students have been able to take advantage of reading materials in the library Soeman to seek collection of books he needed. And the role of libraries Soeman HS has shown consistency in realizing the mission of which is to increase the interest and reading culture for the community.Key Words: Library, Reading, Reading Interest